Prognozirovanie i ocenka rezul'tatov vystuplenij nacional'nych sbornych komand na cempionatach mira po dzjudo na osnovanii ich dostiženij na meždunarodnych turnirach - Timofeev, V. D. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents analyzes 219 results of performances of men`s and 184 women`s national judo teams, which were presented in the final protocols (1-3, 5 and 7 places) at the world championships and Judo World Tour tournaments in four seasons. A highcorrelation was revealed (r = 0,7-0,8, p < 0,005) between the average values of the number of athletes in the final protocols (1-3, 5 and 7 places) of the Judo World Tour and the number of athletes in the final protocols at the World Championships. A high correlation is observed in each of the four seasons analyzed. The total indicators of the number of winners (1-3 places) and the total number of athletes who took 1st to 7th place are more preferable for predicting the performances of teams at the World Championships. It is shown that forecasts remain informative when using any of the linear regression equations for previous seasons. These facts indicate a significant influence of the competitive reliability of the teams performances in a season (the success of their performances in international tournaments) on the results at the main start. However, an analysis of the regression residues indicates that a significant number of national team results deviate from the regressionline by more than 0.5 standard equation errors. This can be explained by the influence of other factors on the success of the performance at the World Championships. First of all, the effectiveness of direct preparation for the main start of the season is among these factors. The influence of competitive reliability and other factors on the performance of 14 national teams at two World Championships was evaluated based on an analysis of the regression residuals (value, sign)